Dental Considerations in Children with Glucose-6-phosphate Dehydrogenase Deficiency (Favism): A Review of the Literature and Case Report - Daniela Hernández-Pérez; Claudia Butrón-Téllez Girón; Socorro Ruiz-Rodríguez; Arturo Garrocho-Rangel; Amaury Pozos-Guillén (Case Reports in Dentistry)
Glucose-6-phosphate dehydrogenase (G6PD) deficiency is an uncommon inherited enzyme deficiency characterized by hemolytic anemia, caused by the inability of erythrocytes to detoxify oxidizing agents such as drugs, infectious diseases, or fava bean ingestion. In this later case, the disorder is known as favism. The aim of the present report was to present a review of the literature in this disease, to describe a case report concerning an affected 9-year-old male, and to review the main implications and precautions in pediatric dental management.